Commitment Organization Ditinjau Dari Work Life Balance, Perceived Organizational Support , Dan Development Career Melalui Job Satisfaction Sebagai Variabel Intervening Pada PT Global Indonesia Asia Sejahtera Medan - Handayani, Sri Putri; Azhmy, Muhammad Fauzan; Aditi, Bunga (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to examine Commitment Organization in terms of Work Life Balance, Perceived Organizational Support and Career Development Through Job Satisfaction Variable Intervening at PT Global Indonesia Asia Sejahtera. The sample collection method is a saturated samplewith a total sample of 104 people. The data analysis method used is path analysis using computer assistance with SPSS version 21 software program the data collection technique uses a Likert scale.The results obtained are work life balance (X1)directly affects job satisfaction (Y1), perceived organizational support (X2)directly affects job satisfaction (Y1), Development Career (X3) directlyaffects on job satisfaction (Y1), work life balance (X1) has no direct effect on organizational commitment (Y2), Perceived organizational support (X2) directly affects organizational commitment (Y2), Career development (X3) directly affects organizational commitment (Y2), job satisfaction (Y1) directly affects organizational commitment (Y2), work life balance (X1) indirectly through job satisfaction (Y1) has a significant influence on organizational commitment (Y2), Perceived organizational support (X2) indirectly through job satisfaction (Y1apositive and significant effect on organizational commitment (Y2). Career development (X3) indirectly through job satisfaction (Y1) has a positive and significant effect on organizational commitment (Y2).